Vida e trabalho em uma perspectiva longeva : atenção aos trabalhadores autônomos - Anusz, Yasmine Komeroski (2014)
The Self-employed workers have as a striking characteristic their autonomy toward their work issues. This come to determine, in many times, a lack of network supporting, which could provide support and care to this work category. In this context, a question emerges: What are the implications of living and aging for these workers? The aim of this work was to understand how the self-employed workers perceive the implications of process of living and aging as self-employed. It was adopted a qualitative approach with exploratory and descriptive nature. The selection for the people for this research was done according to the inclusion criteria, which are: to be a self-employed workers, but not liberal professions; to be a Passo Fundo (RS) resident; to be between 30 and 59 years old; to have worked at least a year as selfemployed; and to accept to be a voluntarily participant in this research. Thus, fourteen self-employed workers were interviewed according to a guiding script. The interviews were recorded and transcribed fully. For the interpretation of the data, it was used the method of content analysis. This study has been approved by the Research Ethics Committee of the University of Passo Fundo. The results found in this research are described in the Scientific Production I entitled The perspectives for self-employed workers on their living and aging , presented in this master s thesis. In order to develop this study, it was segmented accordingly to the objective presented. However the data collected support another study, which will approach the implications of being autonomous in the perspective of those workers